Avaliação das patologias do sistema predial sanitário de prédio comercial, no bairro Betânia, Manaus-AM - Sanchez, Victor Maia (Brasil, 2022)
The sanitary building installations have the function of collecting the waste from the devices and leading them, through pipes, to the public sanitary sewage collection network or to a private treatment system if there is no public collection network. Thus, it is necessary to assess how these facilities are being built and maintained in order to ensure their proper functioning. In this sense, this study aimed to evaluate the pathologies of the sanitary building system of the commercial building in the Betânia neighborhood, Manaus/AM. Therefore, a theoretical and documentary research was carried out on the sanitary sewage facilities and data collection in the commercial building to analyze the existing sanitary system and with that indicate solutions and improvements for the sanitary system studied. The present study consisted of applied research, of an exploratory and descriptive nature, with results treated in a qualitative and quantitative way, together with the theoretical contribution. Based on the collection of information throughout the study, analysis of the commercial building project, application of a questionnaire with users, it was possible to observe that the perception of users about the facilities can be used as an indicator of pathologies, absence of a sanitary installations project has a negative impact on the performance of the sanitary system, making maintenance difficult and contributing to the emergence of various failures such as leaks, odors and clogs. Another aspect is still associated with the use of unskilled labor both in the execution of the work and in the maintenance which can also cause several problems in the sanitary building installation. And, finally, the importance of following the established in technical norms, the NBR 8160:1999 and NBR 14037:2011, and the local legislation, the pró-Águas Law and the Sanitary Code of the municipality of Manaus because they provide the increase the useful life of the facilities and reduce the number of pathologies in the building.